2022
DOI: 10.1177/15330338221085358
|View full text |Cite
|
Sign up to set email alerts
|

Generating synthesized computed tomography from CBCT using a conditional generative adversarial network for head and neck cancer patients

Abstract: Purpose: To overcome the imaging artifacts and Hounsfield unit inaccuracy limitations of cone-beam computed tomography, a conditional generative adversarial network is proposed to synthesize high-quality computed tomography-like images from cone-beam computed tomography images. Methods: A total of 120 paired cone-beam computed tomography and computed tomography scans of patients with head and neck cancer who were treated during January 2019 and December 2020 retrospectively collected; the scans of 90 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
(58 reference statements)
2
7
0
Order By: Relevance
“…Moreover, the HU profile of sCT images in most regions, especially SCT2, was closer to that of RCT images. It indicated that the HU value of SCT1 and SCT2 images were adequately corrected to that of RCT images, consistent with previous studies 19 , 31 . The MAE was significantly less in SCT2 than SCT1 (83.51 vs. 105.62, P < 0.05), indicating improvement was achieved by training with HU corrected CBCT images.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the HU profile of sCT images in most regions, especially SCT2, was closer to that of RCT images. It indicated that the HU value of SCT1 and SCT2 images were adequately corrected to that of RCT images, consistent with previous studies 19 , 31 . The MAE was significantly less in SCT2 than SCT1 (83.51 vs. 105.62, P < 0.05), indicating improvement was achieved by training with HU corrected CBCT images.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the HU pro le of STC images in different regions, especially SCT2, was closer to that of RCT images. It indicated that HU value of SCT1 and SCT2 images were well corrected to that of RCT images, consistent with previous studies 18,30 . It's worth noting that the MAE of SCT2 was signi cantly less than that of SCT1 (83.51 versus 105.62, P < 0.05), indicating that the training result may be improved by training with corrected CBCT images.…”
supporting
confidence: 91%
“…At last, cGAN will be trained for this task. 27 As shown in Figure 1d, cGAN does not require cycle-consistency so will not preserve strong artifact features of CBCT and incorporates CBCT as a conditional input for discriminator to enhance network learning. The generator and discriminator of cGAN are consistent with those of cycleGAN in the second method for subsequent comparison.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…At last, cGAN will be trained for this task 27 . As shown in Figure 1d, cGAN does not require cycle‐consistency so will not preserve strong artifact features of CBCT and incorporates CBCT as a conditional input for discriminator to enhance network learning.…”
Section: Methodsmentioning
confidence: 99%